The development and evaluation of a metacognitive programme for young learners in the South African context - Benjamin, Louis (University of the Western Cape, 2013)
Doctor Educationis === The Basic Concepts Mediated Learning Programme (BCMLP) was developed to enhance the cognitive and scholastic functioning of learners who experience barriers to learning in the early years of schooling in the South African context. The study aimed to initiate a process of evaluation of the efficacy of this metacognitive programme with Grade 2 learners from the ‘Cape Flats’, an historically disadvantaged community in Cape Town. The study was conducted simultaneously in two local education authorities by independent teams of fieldworkers in each of the education authorities. This quantitative, quasi-experimental, non-equivalent comparison group design study was implemented with learners who were equally assigned to an Experimental group (N=54) or Comparison group (N=55). English home-language and Bilingual (English and Afrikaans) learners made up a majority of the study sample. The study was conducted in English.